苏轼晚年岭南时期（1094-1100）及其“和陶诗”之研究 (A Study Of “Poems In Reply To Tao Yuanming” By Su Shi In His Later Years In Lingnan (1094-1100)) - Chin, Yuon Loong (2019)
In Su Shi’s later years during the Song Dynasty, he can never satisfy with his career life, therefore he transferred to Hangzhou, Yingzhou, Yangzhou and Dingzhou. His first creation of Poems in Reply to Tao Yuan-Ming began since when he was in Yangzhou. Unfortunately, Su Shi was banished by the emperor to Lingnan area which was Huizhou and later to Hainan during Shaosheng period, and this was a strike to his life. This dissertation firstly aims on the background and analysis of Su Shi’s creation Poems in Reply to Tao Yuan-Ming since he was in Yangzhou until he came out with the thought to complete Poem in Reply to Tao Yuan-Ming in Huizhou, and lastly immerse in the creation which he used to bring along the collection of poems by Tao Yuan-Ming whenever he went in Hainan. Through the exposition of Poems in Reply to Tao Yuan-Ming which reflects Su Shi’s life experience, this will reflect the relations between Su Shi’s life in Lingnan and his creation. Above analysis will then discusses the relation among Su Shi’s poem, prose and Poems in Reply to Tao Yuan-Ming during Lingnan period. In connection with the classification of theme and content of Poems in Reply to Tao Yuan-Ming, this dissertation also refer commentary against Poems in Reply to Tao Yuan-Ming to lead to a better understanding on how Su Shi overcome his anxiety and hardship in Lingnan. Lastly, this dissertation comes to the conclusion through the comparison of Poems in Reply to Tao Yuan-Ming between the two different periods when Su Shi created them in Huizhou and vii Hainan to understand the differences in life experiences and thoughts of the creations among Su Shi and Tao Yuan-Ming in order to study the way of Su Shi imitating Tao Yuan-Ming and bringing out the life value beyond his difficulties in Lingnan.